2004
DOI: 10.1007/s00423-004-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

HMGI(Y) gene expression as a potential marker of thyroid follicular carcinoma

Abstract: On the basis of our study, we conclude that HMGI(Y) gene expression analysis could be helpful in differentiation between follicular carcinoma and adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Other studies suggested the expression of HMGA1 as a suitable genetic marker to distinguish benign from malignant thyroid tumors (Chiappetta et al, 1995(Chiappetta et al, , 1998Berlingieri et al, 2002;Czyz et al, 2004). As for the RT-PCR analyses, one main disadvantage of HMGA1 is the existence of several retropseudogenes, which can lead to false-positive results in quantification experiments when RNA extractions are contaminated with genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested the expression of HMGA1 as a suitable genetic marker to distinguish benign from malignant thyroid tumors (Chiappetta et al, 1995(Chiappetta et al, , 1998Berlingieri et al, 2002;Czyz et al, 2004). As for the RT-PCR analyses, one main disadvantage of HMGA1 is the existence of several retropseudogenes, which can lead to false-positive results in quantification experiments when RNA extractions are contaminated with genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Many immediate- and delayed-early genes are required by cells to traverse the G1/S boundary of the cell cycle and function as oncogenes when aberrantly expressed. Further studies uncovered high levels of HMGA1 expression at the mRNA or protein level in human cancer cells or primary tumors from diverse tissues, including thyroid [45–48], lung [4951], breast [5259, 117], bladder [58], prostate [6062], colon [63–68], pancreas [69–74], uterine corpus [75], uterine cervix [76], kidney [77], head and neck [78], nervous system [58, 79–84], stomach [85, 86], liver [87], and hematopoietic system [8893, 118, 119]. HMGA1 expression is low or undetectable in normal tissue counterparts.…”
Section: Hmga1 Is Up-regulated In Rapidly Proliferating Cells and Camentioning
confidence: 99%
“…They form stereo-specific, multiprotein complexes termed “enhanceosomes” on the promoter/enhancer regions of genes, where they bind to the minor groove of AT-rich DNA sequences 3,5. HMGA1 proteins are overexpressed in a range of human cancers 69. By using a small sample of tumor tissues, Abe and colleagues previously demonstrated that HMGA1 is overexpressed in pancreatic cancers, although the clinical relevance of HMGA1 expression in this tumor type remains uncertain 10.…”
mentioning
confidence: 99%